Expression of Human Mutant Huntingtin Protein in Drosophila Hemocytes Impairs Immune Responses - Lin, Yu-Hsien; Maaroufi, Houda Ouns; Ibrahim, Emad; Kucerova, Lucie; Zurovec, Michal (Frontiers in Immunology, 2019)
The pathogenic effect of mutant HTT (mHTT) which causes Huntington disease (HD) are not restricted to nervous system. Such phenotypes include aberrant immune responses observed in the HD models. However, it is still unclear how this immune dysregulation influences the innate immune response against pathogenic infection. In the present study, we used transgenic Drosophila melanogaster expressing mutant HTT protein (mHTT) with hemocyte-specific drivers and examined the immune responses and hemocyte function. We found that mHTT expression in the hemocytes did not affect fly viability, but the numbers of circulating hemocytes were significantly decreased. Consequently, we observed that the expression of mHTT in the hemocytes compromised the immune responses including clot formation and encapsulation which lead to the increased susceptibility to entomopathogenic nematode and parasitoid wasp infections. In addition, mHTT expression in Drosophila macrophage-like S2 cells in vitro reduced ATP levels, phagocytic activity and the induction of antimicrobial peptides. Further effects observed in mHTT-expressing cells included the altered production of cytokines and activation of JAK/STAT signaling. The present study shows that the expression of mHTT in Drosophila hemocytes causes deficient cellular and humoral immune responses against invading pathogens. Our findings provide the insight into the pathogenic effects of mHTT in the immune cells.